The Relationship Between Knowledge Level and Dengue Fever Incidence in Areas Exposed and Unexposed to Wolbachia in Bantul Regency Yogyakarta, Indonesia - Rofik Mu’tiya Nuruddin; Tri Wulandari Kesetyaningsih (CV. Inara, 2026)
Indonesia, cases of Dengue Hemorrhagic Fever (DHF) are increasing, with the Bantul Regency having the highest number of cases in Yogyakarta. The method of controlling dengue vectors based on Wolbachia has been proven to be effective in reducing DHF cases. Public knowledge and prevention efforts are very important in reducing the disease. This study aims to compare the level of knowledge and number of dengue fever incidents between areas that have been exposed to the Wolbachia program and those that have not been exposed to it in Bantul Regency, Yogyakarta. The research used an analytical observational approach with a cross-sectional design. The study was conducted in 2023 - 2024. Data DHF incident was from 2018-2023, and knowledge data obtained from questionnaire. Data analysis was carried out using the Mann-Whitney test and the point-biserial correlation test. The knowledge of non-exposed to Wolbachia (83.77) was higher than the exposed to Wolbachia (82.49), but not significant (p=0.149). There was no significant difference in DHF incidence (2018-2023) between two areas (p=0.229). There was a significant correlation between knowledge and DHF incidence in areas exposed to Wolbachia (p=0.015; r = -0.236), and no significant correlation in non-exposed to Wolbachia (p=0.164; r = -0.136). There was no difference in the knowledge and incidence of dengue fever between groups that had not been exposed to Wolbachia and those that had been exposed. Wolbachia release programs together with increased knowledge can sharpen the decline in dengue fever incidence.